The Effect of Students Team Achievement Divisions (STAD) Teaching Method and Small Group Discussion Method on Students’ Writing Descriptive Text Achievement - Sinaga, Riandi; Tampubolon, Sahlan; Sinambela, Erika (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research presents a research report on the using of Students Team Achievement Divisions (STAD) Method and Small Group Discussion Method for students’ writing skill at SMK Kesehatan Tridarma. The objectives are to find out the effect of using Students Team Achievement Divisions (STAD) Method and Small Group Discussion (SGD) Method for students’ writing skill and which method is the most effective one. The subject of this study was grade X students of Senior High School SMK Kesehatan Tridarma. In this study the writer took 100 students of SMK Kesehatan tridarma a as the sample. They were divided into three groups. The first and the second groups are (Experimental Group). They were taught by using Students Team Achievement Divisions (STAD) Method and Small Group Discussion (SGD) method in writing text, while the third group (Control Group) was taught without using Students Team Achievement Divisions (STAD) Method and Small Group Discussion method. The technique for data analysis is quantitative research. In analyzing the data the mean of the students score for pre-test in experimental group one (STAD Method) is 69.27 and the mean of the students score for post-test in experimental group one is 81.30. The mean of the students score for pre-test in experimental group two (SGD Method) is 68, 83 and the mean of the students score for post-test in experimental group two is 80, 29.The mean for pre-test in control group is 66, 8 and the mean for post-test in control group is 76.77 The conclusion is that the using of Students Team Achievement Divisions (STAD) Method and Small Group Discussion are significantly affect the students’ writing skill. STAD Method is the most effective one in teaching news item text than SGD Method. It is suggested that teachers should apply this method as one of methods to improve students’ ability in writing descriptive text.